Students' Attitudes towards Teachers: The Importance of Education as a Means to Address Ethical Challenges in Schools - Suci Rahmadhani; Annisaul Khairat (FITK UIN Walisongo Semarang, 2024)
In the school environment, students' attitudes towards teachers and the relationship between them are key factors that influence the effectiveness of learning and the learning situation in the classroom. There are often ethical challenges such as lack of respect for teachers, behavioral disruptions, and poor communication issues between teachers and students. The purpose of the research is to explore the importance of education as an effective instrument, address the ethical challenges that commonly arise in the school environment and provide insight into the role of education in shaping more positive student attitudes by creating a more ethical learning environment. The method that researchers use is to combine a Quantitative approach by distributing questionnaires to respondents using the Google Form platform and then sharing them online via the WhatsApp application to analyze and obtain accurate data so as to obtain reliable results. The result of this study is that education plays an important role in overcoming ethical challenges in schools by developing students' character and strengthening positive attitudes towards teachers. Moreover, the strategy that can overcome these problems is communication between teachers and students. The researcher hopes that future researchers will be able to contribute to the ethical challenges in schools more precisely related to students' attitudes towards teachers. In addition, the researcher also hopes that this research can be a foundation for everyone so that they can appreciate how important education is to ethical attitudes, so that it can give birth to a young generation that grows responsibly in society. The researcher also suggests other researchers to further investigate it by focusing more on the character building of students towards teachers as well as investigating more efficient educational programs.